2008
DOI: 10.1021/jm701606b
|View full text |Cite
|
Sign up to set email alerts
|

A Series of Potent and Selective, Triazolylphenyl-Based Histone Deacetylases Inhibitors with Activity against Pancreatic Cancer Cells and Plasmodium falciparum

Abstract: The discovery of the rules governing the inhibition of the various HDAC isoforms is likely to be key to identifying improved therapeutics that act as epigenetic modulators of gene transcription. Herein we present results on the modification of the CAP region of a set of triazolylphenyl-based HDACIs, and show that the nature of substitution on the phenyl ring plays a role in their selectivity for HDAC1 versus HDAC6, with low to moderate selectivity (2-51-fold) being achieved. In light of the valuable selectivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
99
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(105 citation statements)
references
References 52 publications
6
99
0
Order By: Relevance
“…WR301801 exhibited an IC 50 of 10 nM in the mammalian HDAC inhibition assay (Fig. 2), confirming the results of earlier studies (9,23).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…WR301801 exhibited an IC 50 of 10 nM in the mammalian HDAC inhibition assay (Fig. 2), confirming the results of earlier studies (9,23).…”
Section: Resultssupporting
confidence: 89%
“…We have not yet considered the issue of the mechanism of action, toxicity, and selectivity in detail. Earlier studies have shown that WR301801 is a nM inhibitor of mammalian HDAC (9,23). This was confirmed in a functional assay here (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…223 1,5-Triazole derivatives have shown activity against numerous cancer cell lines, 205,215,[224][225][226][227] and against the parasites Trypanosoma cruzi 70,228 and Plasmodium falciparum. 205 They have also been employed in the search for new antimicrobiotics 229 and antifungal agents. 230 Institute's panel screen (NCI-60 panel) compared to vorinostat and dasatinib.…”
Section: Target-oriented Medicinal Chemistrymentioning
confidence: 99%
“…256 SAHA, clinically approved to treat persistent or refractory T-cell lymphoma, inhibits growth of P. falciparum D6 and W2 strains with IC 50 values of 247 and 161 nM, respectively. 256 One of SAHA's derivatives (188, Figure 105) was found to be about 14-and 5-fold more active than its parent compound, with IC 50 values of 17 and 32 nM for P. falciparum D6 and W2, respectively. Similarly, Marfurt et al have disclosed that 2-aminosubericbased HDAC inhibitors present potent in vitro activity against sensitive (3D7) and drug-resistant (K1) P. falciparum strains.…”
Section: Antitumoralsmentioning
confidence: 99%